THE ROLE OF BREASTFEEDING SELF-EFFICACY IN SMOOTH BREASTFEEDING IN BREASTFEEDING MOTHERS IN THE STATE HEALTH CENTER AREA, NORTH LAMPUNG: A CROSS-SECTIONAL STUDY - Fajriah, Asruria Sani; Rini, Suci Muspita; Rohmah, Miftakhur; Astutik, Reni Yuli (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2026)
Exclusive breastfeeding is the provision of breast milk to infants aged 0-6 months without being given additional food or drink other than drugs for therapy (treatment of disease). Exclusive breastfeeding is a form of public health behavior, behavior influenced by predisposing factors, such as knowledge, individuals, attitudes, self Efficacy, traditions, social norms, and other elements contained in individuals and society. The achievement of exclusive breastfeeding in North Lampung district in 2021 was 61.5% with a total of 3,904 babies. Meanwhile, in 2022 it fell to 57.9% with 1,949 babies. The number of exclusive breastfeeding achievements in 2022 in the Gedung Negara health center area is 65%. The achievement target in 2023 is 57%, the achievement in TW II in the Gedung Negara Health Center area is 44%. Design of this reseach Analytical observational study with cross sectional approach. By purposive sampling technique obtained a sample of 32 respondents, independent variables Breastfeeding Self Efficacy using a questionnaire BSES-SF (Breastfeeding Self Efficacy Scale-Short Form) and the dependent variable Smooth Breast Milk with questionnaire. Used statistical tests chi-square to determine the relationship between the two variables . The results of the study from 32 respondents were obtained by most respondents of the High Breastfeeding Self Efficacy criteria as many as 20 respondents (62.5%). And found most respondents of the smooth breast milk criteria as many as 18 respondents (56.3%). Analyzes using Chi-Square statistical test obtained the results of p = 0.01 <0.05 then H0 was rejected and H1 accepted which means there is a relationship between breastfeeding self efficacy on smooth breast milk in breastfeeding mothers in the region Gedung Negara Health Center. Changes in mindset and self-motivation greatly affect the habits and parenting styles for mothers and babies. Family and environmental support is needed to build self- motivation or good self-confidence for mothers during the breastfeeding process.